Effects of Mixing Ratio of Heavily Beaten Pinus merkusii Pulp on Physical Properties of Kraft Acacia nilotica Pulp Sheets - Ganis Lukmandaru; Fajar Setiaji; M. Rena Siagian (Wood Research Journal, 2019)
Paper industries commonly produce pulp sourced from a mixture of pulps, rather than from a single pulp, to obtain desired properties. In addition, the beating process is an essential step with respect to physical properties of pulp. Kraft pine (Pinus merkusii/PM) pulps were beaten to different degrees, i.e 200~300 CSF (heavy-beating) and 300~400 CSF (moderatebeating), paper sheets then were formed from each beaten sample. It was found that the strength properties of prepared paper sheets decreased the longer they were beaten, particularly as seen by the tear index and fold number. By microscopic investigation, it was found that cut or shortened fibers occurred very frequently in the pine pulps. Furthermore, the effects of heavily beaten pine pulp additions on handsheet properties of kraft pulps of Acacia nilotica (AN) were investigated. Four different mixing ratios by weight of AN/PM from 100:0, 90:10, 80:20, and 70:30 during beating, as well as four different kappa numbers of AN pulps (32.5, 34.0, 34.2, and 35.9) were applied. In general, the decrease in strength properties (3~25%) that occurred with increasing pine pulp ratio was more evident between pulp without pine and a 30% ratio of pine pulps. Fold number was reduced considerably (2.8~24.7%) by the blend composition but less pronounced in tear index (3.0~8.9%) from the initial values. However, the 10% or 20% ratio of PM pulps could increase opacity, brightness, and strength properties in some cases. No clear trend was found with increasing kappa number.